Expression of proteinases and inhibitors in human breast cancer progression and survival. Issue 5 (1st October 2002) - Baker, E A; Stephenson, T J; Reed, M W R; Brown, N J
Abstract : Aims: The expression of proteinases and their inhibitors determines the extracellular matrix (ECM) turnover in normal and pathological processes. In cancer, proteolysis is abnormally regulated, favouring ECM degradation, which aids tumour invasion and metastasis. Previous studies have determined the expression of proteinases and inhibitors in breast cancer using a variety of techniques, including immunohistochemistry; however, most have looked at the expression of individual proteinases and/or inhibitors. Therefore, the aim of the current study was to determine the simultaneous cellular expression of matrix metalloproteinases (MMPs), plasminogen activators (PAs), and tissue inhibitors of metalloproteinases (TIMPs) in patients with breast cancer and correlate this with clinical pathological staging and survival. Methods: Immunohistochemistry was used to determine the expression of proteinases (MMP-1, MMP-2, MMP-3, MMP-9, urokinase-type PA, and tissue-type PA) and inhibitors (TIMP-1 and TIMP-2) in 44 patients with breast cancer. Results: The expression of all the factors studied was stronger or equivalent in tumour cells than in fibroblasts or inflammatory cells within the tumour section. Both positive and negative trends have emerged in the correlation between the cellular expression of proteinases and inhibitors and breast tumour pathology (tumour grade, lymphovascular invasion, and Nottingham prognostic index). Conclusions: The interactions between proteinases and their inhibitors in breast cancer progression are complex. Although there are differences in the expression of these factors that relate to differences in breast cancer pathology, there are no outstanding individual factors that consistently correlate with prognosis. Therefore, different factors are probably important at different stages of the process, and the balance in the relative concentrations of proteinases and inhibitors probably determines ECM degradation in breast tumour invasion and metastasis in vivo.